The relationship between three X-linked genes and the risk for hypertension among northeastern Han Chinese - Jinxin Li (Journal of the Renin-Angiotensin-Aldosterone System, 2015)
Background and objective: Incidences of hypertension are increasing and this condition is more common in men than in women. We selected six well-characterized polymorphisms from three X-linked genes (ACE2, AGTR2, apelin) aiming to investigate their interactive association with hypertension among northeastern Han Chinese. Methods and results: This was a case-control study involving 1009 hypertensive patients and 756 normotensive controls. All polymorphisms except rs3761581 in the apelin gene satisfied the Hardy-Weinberg equilibrium in females. The genotype and allele distributions of rs1403543 in the AGTR2 gene and rs56204867 in the apelin gene differed significantly between patients and controls for both genders, even after the Bonferroni correction ( P <0.05/6). The risk prediction was significant for rs1403543 and rs56204867 under both additive and dominant models for both genders. In haplotype analysis, significance was seen for haplotype G-T-G-G-A (alleles in order of rs1978124, rs2106809, rs1403543, rs5194 and rs56204867), which was overrepresented in patients (5.15% versus 1.10% in controls, P Sim =0.004). Interaction analysis indicated that all derived multifactor dimensionality reduction (MDR) models were non-significant for both genders. Conclusion: Our findings demonstrate that genetic defects in AGTR2 and apelin genes by themselves may play an independent leading role in determining susceptibility to hypertension in both genders.